Chemometric Analysis of Ethanol Extract of Breadfruit Leaves (Artocarpus altilis) from Various Regions in Central Java - Yumni, Gharsina Ghaisani; Rini Primitasari; Novi Nur Afifah; Sumantri, Sumantri (Jurnal Kefarmasian Indonesia, 2024)
Breadfruit leaves (Artocarpus altilis) contain chemical compounds, including flavonoids, phenolics, tannins, alkaloids, and saponins, which have antioxidant activity. The planting location causes differences in the composition of active compounds, causing their biological activity to change. This research aimed to determine the highest antioxidant activity, flavonoid, phenolic, and tannin content of 96% ethanol extract of breadfruit leaves from 6 sub-districts in Central Java and to group them using the principal component analysis (PCA) and cluster analysis (CA) chemometric methods. Breadfruit leaves were extracted using the maceration method using 96% ethanol solvent. The antioxidant activity test was carried out using the DPPH method using vitamin C as a comparison. Total flavonoid levels were determined using an AlCl3 reagent. Determination of total phenolic and tannin content levels using Folin-Ciocalteu. Then, chemometric analysis was carried out using Principal Component Analysis (PCA) and Cluster Analysis (CA). The results showed that 96% ethanol extract of breadfruit leaves has the highest IC50, flavonoid, phenolic, and tannin levels, respectively, namely 82.79 ± 0.20 µg/ml; 9,96 ± 0,17 mgQE/g; 603.75 ± 2.6; 123.66 ± 0.76 which came from the Tengaran area. The samples were divided into three groups using PCA and CA methods based on the variables used. The first group was Gajahmungkur, Mranggen, and Pamotan. The second group was Gunungpati and Bandungan. The third group was Tengaran.